Acid mine drainage treatment by integrated submerged membrane distillation–sorption system. (March 2019) - Ryu, Seongchul; Naidu, Gayathri; Hasan Johir, Md Abu; Choi, Youngkwon; Jeong, Sanghyun; Vigneswaran, Saravanamuthu
Abstract: Acid mine drainage (AMD), an acidic effluent characterized by high concentrations of sulfate and heavy metals, is an environmental and economic concern. The performance of an integrated submerged direct contact membrane distillation (DCMD) – zeolite sorption system for AMD treatment was evaluated. The results showed that modified (heat treated) zeolite achieved 26–30% higher removal of heavy metals compared to natural untreated zeolite. Heavy metal sorption by heat treated zeolite followed the order of Fe > Al > Zn > Cu > Ni and the data fitted well to Langmuir and pseudo second order kinetics model. Slight pH adjustment from 2 to 4 significantly increased Fe and Al removal rate (close to 100%) due to a combination of sorption and partial precipitation. An integrated system of submerged DCMD with zeolite for AMD treatment enabled to achieve 50% water recovery in 30 h. The integrated system provided a favourable condition for zeolite to be used in powder form with full contact time. Likewise, heavy metal removal from AMD by zeolite, specifically Fe and Al, mitigated membrane fouling on the surface of the hollow fiber submerged membrane. The integrated system produced high quality fresh water while concentrating sulfuric acid and valuable heavy metals (Cu, Zn and Ni). Graphical abstract: Image 1